Growth and Value Fund Performance Comparison - Lim Min; Aminah Shari; Leah, Tseu Lee Yah; Lovenigasri Rajendran; Shirley Ling; Teo, Qi Mei (Human Resource Management Academic Research Society, 2022)
This article examines and contrasts the performance of small-cap growth and small-cap value funds in the United States. Between May 2016 and May 2022, a total of 139 small-cap growth funds and 97 small-cap value funds were collected via Yahoo Finance. The weekly data was then used to calculate the Treynor ratio, Sharpe ratio, and Jensen alpha. The finding shows that US small-cap value funds appear to be superior to small-cap growth funds. The Sharpe and Treynor ratios demonstrate the higher risk-adjusted performance of small-cap value funds relative to their benchmarks. whereas the Sharpe ratio is the only indicator of outperformance for small-cap growth funds. Regarding the Jensen alpha, value funds possessed positive alphas and outperformed the benchmark. Therefore, the results of this study could aid investors in picking a portfolio with superior risk-adjusted performance.